Cardiac and Kidney Benefits of Empagliflozin in Heart Failure Across the Spectrum of Kidney Function: Insights From EMPEROR-Reduced. Issue 4 (26th January 2021) - Zannad, Faiez; Ferreira, João Pedro; Pocock, Stuart J.; Zeller, Cordula; Anker, Stefan D.; Butler, Javed; Filippatos, Gerasimos; Hauske, Sibylle Jenny; Brueckmann, Martina; Pfarr, Egon; Schnee, Janet; Wanner, Christoph; et al.
Abstract : Background: In EMPEROR-Reduced (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Reduced Ejection Fraction), empagliflozin reduced cardiovascular death or heart failure (HF) hospitalization and total HF hospitalizations, and slowed the progressive decline in kidney function in patients with HF and a reduced ejection fraction, with and without diabetes. We aim to study the effect of empagliflozin on cardiovascular and kidney outcomes across the spectrum of kidney function. Methods: In this prespecified analysis, patients were categorized by the presence or absence of chronic kidney disease (CKD) at baseline (estimated glomerular filtration rate [eGFR] <60 ml/min/1.73 m 2 or albumin-to-creatine ratio >300 mg/g). The primary and key secondary outcomes were: (1) a composite of cardiovascular death or HF hospitalization (primary outcome); (2) total HF hospitalizations; and (3) eGFR slope. The direct impact on kidney events was investigated by a prespecified composite kidney outcome (defined as a sustained profound decline in eGFR, chronic dialysis, or transplant). The median follow-up was 16 months. Results: Of 3730 patients who were randomized to empagliflozin or placebo, 1978 (53%) had CKD. Empagliflozin reduced the primary outcome and total HF hospitalizations in patients with and without CKD: hazard ratio (HR)=0.78 (95% CI, 0.65–0.93) and HR=0.72 (95% CI, 0.58–0.90), respectively (interaction P =0.63). Empagliflozin slowed the slope of eGFR decline by 1.11 (0.23–1.98) ml/min/1.73 m 2 /yr in patients with CKD and by 2.41 (1.49–3.32) ml/min/1.73 m 2 /yr in patients without CKD. The risk of the composite kidney outcome was reduced similarly in patients with and without CKD: HR=0.53 (95% CI, 0.31–0.91) and HR=0.46 (95% CI, 0.22–0.99), respectively. The effect of empagliflozin on the primary composite outcome and key secondary outcomes was consistent across a broad range of baseline kidney function, measured by clinically relevant eGFR subgroups or by albuminuria, including patients with eGFR as low as 20 ml/min/1.73 m 2 . Empagliflozin was well tolerated in CKD patients. Conclusions: In EMPEROR-Reduced, empagliflozin had a beneficial effect on the key efficacy outcomes and slowed the rate of kidney function decline in patients with and without CKD, and regardless of the severity of kidney impairment at baseline. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03057977. Abstract : Supplemental Digital Content is available in the text.